Governor’s Rapids Conservation Research Facility and Recreational Complex center for riverine conservation research and education - Rodimo, Jan Brian T.
The Quirino Province envisions the Governor’s Rapids to be the leading tourist attraction site in the Quirino Province. With having one of the tributaries of the Cagayan River in the municipality of Maddela, the existing tourism facilities cater on the visitors and offer different water activities in its bounds, from river cruising and sightseeing, caving, to spelunking and cliff diving. In this tributary lies the first fish sanctuary management project in Northern Philippines with the assistance of the Zoological Society of London through Eels Project. The proposal Governor’s Rapids Research Facility and Recreational Complex aims to not only further protect the fish sanctuary and protected landscapes in the Governor’s Rapids and boost the tourism industry in Maddela. It is also to propose another alternative planning approach, the “Scientific Tourism”, wherein it targets not only the general tourists but also the scientific community, especially those who focus on riverine and freshwater research. The proposal is to help not only the economic development of the site through ecotourism but also to help the government and the people of Quirino further to study their Quirino Protected Landscapes and the Cagayan River, starting from the Governor’s Rapids. The proposal will be through a facility and spaces that provide services for research, education, information dissemination, and training for the local development of the area. Through scientific tourism approach in the planning of Governor’s Rapids, scientific studies will further reach the gap of knowledge on the status of habitats, biodiversity, and human activities found in the Governor’s Rapids and Quirino Protected Landscapes. The scientific tourism also provides awareness that further improves the enjoyment of outdoor recreation for locals and tourists in Quirino.